2009
DOI: 10.1007/s00404-009-1099-8
|View full text |Cite
|
Sign up to set email alerts
|

Observer accuracy and reproducibility of visual estimation of blood loss in obstetrics: how accurate and consistent are health-care professionals?

Abstract: Visual estimations were inaccurate by health-care professionals who have a tendency to overestimate. Experience did not appear to have a confounding effect on accuracy. Further training in visual assessment skills is necessary in order to improve the clinicians' estimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 12 publications
3
53
2
1
Order By: Relevance
“…(10)(11)(12)(13) Previous studies have reported that, independent of the experience or skill level of healthcare providers, visual estimation of postpartum blood loss has a 25%-89% error of measurement. (5,6,9,14) The present study supports these findings. Similarly, a study by Prasertcharoensuk et al (9) reported error of measurement using visual estimation as compared with direct measurement; however, details of the direct measurement protocol was not explained.…”
Section: Discussionsupporting
confidence: 91%
“…(10)(11)(12)(13) Previous studies have reported that, independent of the experience or skill level of healthcare providers, visual estimation of postpartum blood loss has a 25%-89% error of measurement. (5,6,9,14) The present study supports these findings. Similarly, a study by Prasertcharoensuk et al (9) reported error of measurement using visual estimation as compared with direct measurement; however, details of the direct measurement protocol was not explained.…”
Section: Discussionsupporting
confidence: 91%
“…It is known that without a quantitative measurement method, blood loss is often underestimated. 15,16 The calculation of DHb by measurement before and after delivery poses an objective variable to examine blood loss during birth. Because it is routine in our institution to determine Hb levels in all parturient women before as well as after delivery, no woman with intrahepatic cholestasis of pregnancy and only 15 women in the control group were excluded from analysis as a result of missing DHb.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, investigating the accuracy of the estimation of blood loss during surgery, have shown that such estimations are plagued by a high degree of inaccuracy, with a predominant underestimation [3,[20][21][22]. A potential explanation for Fig.…”
Section: Discussionmentioning
confidence: 95%